Re-Emergence of Usutu Virus and Spreading of West Nile Virus Neuroinvasive Infections During the 2024 Transmission Season in Croatia - Tatjana Vilibić-Čavlek; Ljubo Barbić; Ana Klobučar; Marko Vucelja; Maja Bogdanić; Dario Sabadi; Marko Kutleša; Branimir Gjurašin; Vladimir Stevanović; Marcela Curman Posavec; Linda Bjedov; Marko Boljfetić; et al. (Viruses)
Neuroinvasive arboviruses such as tick-borne encephalitis virus (TBEV), West Nile virus (WNV), Usutu virus (USUV), and Toscana virus (TOSV) have (re-)emerged with increasing incidence and geographic range. We analyzed the epidemiology of arboviral infections in Croatia during the 2024 transmission season. A total of 154 patients with neuroinvasive diseases (NID), 1596 horses, 69 dead birds, and 7726 mosquitoes were tested. Viral RNA was detected using RT-qPCR. IgM/IgG-specific antibodies were detected using commercial ELISA or IFA, with confirmation of cross-reactive samples by virus neutralization test. RT-qPCR-positive samples were Sanger sequenced. Arboviral etiology was confirmed in 33/21.42% of patients with NID. WNV was most frequently detected (17/11.03%), followed by TBEV (10/6.49%), USUV (5/3.24%), and TOSV (1/0.64%). WNV infections were reported in regions previously known as endemic, while in one continental county, WNV was recorded for the first time. USUV infections re-emerged after a six-year absence. In addition to human cases, acute WNV infections were recorded in 11/395 (2.78%) of horses and two dead crows. WNV IgG seropositivity was detected in 276/1168 (23.63%) and TBEV IgG seropositivity in 68/428 (15.88%) horses. None of the tested mosquito pools were positive for WNV and USUV RNA. Phylogenetic analysis showed the circulation of WNV lineage 2 and Usutu Europe 2 lineage. Climate conditions in 2024 in Croatia were classified as extremely warm, which could, at least in part, impact the quite intense arboviral season. The spreading of flaviviruses in Croatia highlights the need for continuous surveillance in humans, animals, and vectors (“One Health”).